Transitivity Analysis of Students' Agency in EFL High School Students’ Recount Text - Shahnaz Marshanda Putri; Galuh Kirana Dwi Areni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This qualitative descriptive study examines how 33 EFL high school students in Semarang construct their agency through language in recount texts written about their shared classroom learning experience. Guided by Halliday and Matthiessen’s (2014) Systemic Functional Linguistics transitivity framework and Van Leeuwen’s (1996) Social Actor Representation theory, a total of 327 clauses were analyzed across two phases: transitivity parsing and agency identification. Findings reveal that mental processes were the most dominant process type (f=125), followed by relational (f=94), material (f=58), verbal (f=44), existential (f=4), and behavioral (f=2) processes. In terms of agency, activation (f=220) substantially outweighed passivation (f=103), indicating that students primarily positioned themselves as active, conscious experiencers—particularly as Sensers in mental clauses—despite being materially passivated as recipients of the teacher’s instructional actions. This “split-domain agency” pattern reveals a form of hidden agency that surface-level grammatical analysis alone would overlook. The findings contribute to the understanding of student-centered learning and highlight the value of combining transitivity analysis with social actor representation in uncovering EFL learners’ agentive voices in written texts. Keywords: EFL, Recount text, Student Agency, Transitivity Analysis, Writing Skill